Organoleptic Test Of Whole Wheat Flour For Quality Wingko Babat - Tanpili, Harum Caisar; Andriani, Cici; Fridayati, Lucy; Indrayeni, Wiwik (Universitas Negeri Padang, 2025)
This research was motivated by the absence of research on the effect of whole wheat flour substitution on the quality of wingko tripe. This research analyzes the impact of entire wheat flour substitution of 20%, 35%, and 50% on the quality of shape, color, aroma, texture, and taste of wingko tripe. This type of research is experimental, namely conducting a direct experiment on the effect of whole wheat flour substitution on the quality of wingko tripe, and was repeated three (3) times. The data type is primary data sourced from 3 expert panelists who filled in the organoleptic test format. The analysis technique used is binominal data analysis which looks at whether there is a significant difference between the treatments and then uses analysis of variance (ANOVA) to analyze the organoleptic test data. The results of the analysis of variance show sig <0.05, which means that HO is rejected and HA is accepted, so there is a significant effect, therefore the Duncan test will be continued. The substitution of whole wheat flour affects the quality of taste (wheat) and the results of the wingko tripe quality test for the best whole wheat flour are found in treatment X3 with a 50% substitution of whole wheat flour.